The soldier experience in the fourteenth century - Bell, Adrian R. 1971-; Curry, Anne; Chapman, Adam; King, Andy 1963-; Simpkin, David (Boydell & Brewer, 2011)
The "long" fourteenth century saw England fighting wars on a number of diverse fronts - not just abroad, in the Hundred Years War, but closer to home. But while tactics, battles, and logistics have been frequently discussed, the actual "experience" of being a soldier has been less often studied. Via a careful re-evaluation of original sources, and the use of innovative methodological techniques such as statistical analysis and the use of relational databases, the essays here bring new insights to bear on soldiers, both as individuals and as groups. Topics addressed include military service and the dynamics of recruitment; the social composition of the armies; the question of whether soldiers saw their role as a "profession"; and the experience of prisoners of war. Contributors: Andrew Ayton, David Simpkin, Andrew Spencer, David Bachrach, Iain MacInnes, Adam Chapman, Michael Jones, Guilhem Pepin, Remy Ambuhl, Adrian R. Bell